The Effect Of Keroncong Music Therapy On The Reduction Of Pain Intensity In Post-Trauma Patients - Septafani, Oktaffrastya Widhamurti; Rahman, Sonu Eky Reza; Purwandari, Henny (STRADA : Jurnal Ilmiah Kesehatan, 2021)
One therapy that can reduce pain intensity is keroncong music therapy. The purpose of this study was to determine the effect of keroncong music therapy on reducing pain intensity in post trauma patients at RSUD Nganjuk. This study used a pre-experimental research design with the One Group Pre-Post Test Design approach.The population that met the inclusion criteria. The number of samples is 22 respondents with purposive sampling technique. The results of the study from 22 respondents, before being given therapy almost all respondents were 18 respondents with severe pain intensity (82%), while the intensity of pain after being given music therapy most respondents were 15 respondents with moderate pain intensity (68%). The Wilcoxon test results obtained pvalue = 0,000 α = (0,05), so H1 was accepted. This shows that there is an influence of keroncong music therapy on the reduction in pain intensity in post trauma patients in RSUD Nganjuk.